Relation between Acute GVHD and NK Cell Subset Reconstitution Following Allogeneic Stem Cell Transplantation - Ullrich, Evelyn; Salzmann-Manrique, Emilia; Bakhtiar, Shahrzad; Bremm, Melanie; Gerstner, Stephanie; Herrmann, Eva; Bader, Peter; Hoffmann, Petra; Holler, Ernst; Edinger, Matthias; Wolff, Daniel (Frontiers in Immunology, 2016)
One of the major challenges of allogeneic stem cell transplantation (allo-SCT) is to reduce the risk of graft-versus-host disease (GVHD) while boosting the graft-versus-leukemia effect (GVL). The reconstitution of natural killer (NK) cells following allo-SCT is of notable interest due to their known capability to induce GVL without GVHD. Here, in this study, we investigate the association between the incidence and severity of acute GVHD (aGVHD) and the early reconstitution of NK cell subsets following allo-SCT. We analyzed 342 samples from 107 patients using flow cytometry, with a focus on immature CD56high and mature cytotoxic CD56dim NK cells. Longitudinal analysis of immune reconstitution after allo-SCT showed that the incidence of aGVHD was associated with a delayed expansion of the entire NK cell population, in particular the CD56high subset. Notably, the disturbed reconstitution of the CD56high NK cells also correlated with the severity of aGVHD.